States of emergence: Writing African female same-sex sexuality. Issue 2 (3rd April 2017) - Munro, Brenna M.
ABSTRACT: Tracing a series of intertextually linked short stories from the 1990s to the present by women writers from Nigeria and its diaspora—Chimamanda Ngozi Adichie, Unoma Azuah, Chinelo Okparanta, and Lola Shoneyin—I suggest that although the figure of the African lesbian appears "new" in the context of heightened contemporary attention to the issue of homosexuality, this figure has a literary history. Ghanaian Ama Ata Aidoo's novel Our Sister Killjoy: Or, Reflections From A Black-Eyed Squint (1977) inaugurates this formation, in which the imagining of female same-sex desire is entangled with articulating the experience of migration under the shadow of imperial histories. In these short stories, the emphasis on the difficulties of love in puritanical times and transnational places produces the figure of the African lesbian as a symbol of appealingly human vulnerability, resilience, and complexity.